Regulação e agências no ordenamento jurídico brasileiro - Malavazi, Alício; Sá, Maria da Conceição Alves; Armelin, Priscila Kutne; Carneiro, Vivalda Sueli Borges (Revista Jurídica Cesumar: Mestrado (Online), 2007)
o